Opposing Roles of Wnt Inhibitors IGFBP-4 and Dkk1 in Cardiac Ischemia by Differential Targeting of LRP5/6 and β-catenin - Liman QIU; Da WO; Weidong ZHU (康复学报)
Abnormal activation of Wnt canonical signaling pathway is involved in the development and progression of various diseases, such as ischemic heart disease. Therefore, inhibiting the activation of Wnt signaling is likely to be beneficial for preventing the worsening of ischemic heart disease. Although, our research results revealed an interesting phenomenon: two separate secretory Wnt signaling inhibitors, IGFBP-4 and Dkk1, had drastically opposing effects on cardiomyocytes following cardiac ischemia. Further in-depth research have revealed that surprisingly, Wnt canonical signaling receptors LRP5/6, as well as intracellular β-catenin played crucial roles in the regulation of signal transductions following myocardial ischemia. These insights have allowed us to not only better understand the regulation of Wnt canonical signaling pathway, but also provide a promising and novel initiative for the clinical treatment of myocardial infarction.